ANALISIS ISU DAN CAPAIAN PEMBANGUNAN GENDER BIDANG PENDIDIKAN DI KABUPATEN BANYUMAS - Soetji Lestari (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2017)
Abstract :This paper aims to identify gender issues and educationalgender development outcomes in Banyumas Regency in BanyumasRegency. This study is interesting because the Gender Development Index(GDI) and Human Development Index (HDI) of Banyumas Regency in 2015still show disparity. Education is one element of the three components thatform the basis of HDI calculation, in addition to health and economics. Thispaper is a literature study based on main documents, namely Banyumas onFigures, SIGA Banyumas, Banyumas Regency’s Work Program Plan, andso on. The results of show that gender issues in education, namely; 1) at theage of elementary / junior high school children, more girls have not schoolthan boys; 2) not all school-age children at a certain level of education canenjoy education at that level; 3) men and women in certain age groups arenot yet literate; 4) number of female school participation aged 7-24 have notbeen equivalent to male in that age group. In fact, not all of the educationpolicy in Banyumas Regency is gender indicative. The implication of thisresults is the achievement of gender education development in BanyumasRegency still needs to be improved continuously and supported by synergybetween local government, school and community. Abstrak : Tulisan ini bertujuan untuk mengidentifikasi isu gender dan capaian pembangunan gender bidang pendidikan di Kabupaten Banyumas.Studi tentang hal tersebut menarik karena Gender Development Index(GDI) dan Human Development Index (HDI) Kabupaten Banyumas (2015)masih menunjukkan disparitas. Pendidikan adalah salah satu unsur daritiga komponen yang menjadi dasar penghitungan HDI, selain kesehatandan ekonomi. Tulisan ini merupakan studi pustaka yang bersumber daridokumen utama seperti Banyumas dalam Angka, SIGA Banyumas,Rencana Program Kerja Kabupaten Banyumas, dan sebagainya. Hasilstudi menunjukkan bahwa persoalan gender bidang pendidikan, yaitu;1) pada usia anak SD/MI, lebih banyak anak perempuan yang tidaksekolah dibanding ana laki-laki; 2) belum semua anak usia sekolah padajenjang pendidikan tertentu dapat menikmati pendidikan pada jenjangtersebut; 3) laki-laki maupun perempuan pada kelompok usia tertentubelum seratus persen melek huruf ; 4) angka tingkat partisipasi sekolahperempuan usia 7-24 belum setara dengan laki-laki dalam kelompok usiatersebut. Pada kenyataannya, belum seluruh dari kebijakan pendidikandi Kabupaten Banyumas bersifat indikatif gender. Implikasinya, capaianpembangunan gender bidang pendidikan di Kabupaten Banyumas masihperlu ditingkatkan secara terus-menerus dan didukung oleh sinergi antarapemerintah daerah, sekolah, dan masyarakat.